Treatment-seeking behavior for sexually transmitted infections in a high-risk population - Rosenheck, Rachel; Ngilangwa, David; Manongi, Rachael; Kapiga, Saidi (AIDS care, 2010)
The World Health Organization estimates that 340 million new cases of curable sexually transmitted infections (STIs) occur every year, while 33 million individuals are estimated to be living with HIV. The AIDS and STI epidemics are not independent with untreated STIs increasing HIV acquisition and transmission. Female sex workers have increased prevalence of untreated STIs and have been hypothesized to affect the health and HIV incidence of the general population. This paper aims to investigate why some female sex workers who experience symptoms of vaginal discharge or genital ulcers seek treatment while others do not. Data were collected from a cohort study conducted between 2002 and 2005 among female bar and hotel workers in Moshi, Tanzania. Study subjects were recruited from 7 out of 15 administrative wards in Moshi as part of the Moshi's Women's Health Project. Data were restricted to women self-reporting symptoms of vaginal discharge or genital ulcers (n=459) within the past year. Logistic regression was performed with SAS 9.1. Qualitative analysis was performed using in-depth interviews and focus group discussions among a convenience sample (n=42) of women already enrolled in the study. All interviews and focus group discussions were tape-recorded and transcribed, and data were analyzed thematically. Sixty-four percent of the sample sought treatment for either ailment. Multivariate analysis identified relationship to man of last sexual intercourse, ever experiencing a pregnancy, and age as significant predictors to seeking treatment. Four salient themes of threats to fertility, stigma correlated with prostitution, discomfort with the physical exam, and perceived views of clients were revealed as predictors to why women seek or intentionally ignore symptoms. Understanding the motivations and barriers for seeking treatment of STIs has far ranging public health implications that could help curtail the unnecessary associated morbidity and mortality and curtail the transmission of HIV.